Pengaruh Model Pembelajaran CORE Dengan Berbantuan Media Crossword Puzzle Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran IPS Kelas VII SMPN 2 Takengon - Ayuni*, Maulida; Kusnafizal, Teuku; Kesuma, Teuku Bahagia (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to determine the effect of the CORE (Connecting, Orgenaizing, Reflecting and Extending) learning model with the help of Crossword puzzele media on learning motivation. This study uses a quantitative approach with a type of experimental research that is True design experiments designed Postttest-only control dsign. The population in this study was grade VII students of SMPN 2 Takengon with a sample of grade VII 1 and VII 2 of 30 people each. Data collection techniques in this study used observation and questionnaires. For analysis techniques using linear regression and tests Hypothesis. Based on the results of research from regression tests, student motivation increased by 35% based on observation and based on questionnaires 39%, the correlation value of 3.18 on Constant 57.33 was influenced by external and environmental factors. The results of the hypothesis test or t test obtained tcount table or 5.291 2.048at a significant level () 5% then Ha is accepted. For the value of the product moment correlation coefficient of 0.883 shows very strong. Therefore, the CORE learning model assisted by Crossword Puzzle media can increase social studies learning motivation of grade VII1 students of SMPN 2 Takengon.